Workshop: Writing Techniques Scientific Papers as an Improvement Effort Competency of Physical Education, Sports, and Health (PJOK) Teachers in the District of Tasikmalaya - Ivan Rivan Firdaus; Berliana; Sagitarius; Widi Kusumah; Mona Fiametta Febrianty (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The purpose of this community service activity provided training techniques for writing scientific works to teachers of Physical Education, Sports, and Health (PJOK) in the district of Tasikmalaya. This program is followed by 30 teachers of PJOK in the District of Tasikmalaya who are members of the National Sports Teachers' Association (IGORNAS) in Tasikmalaya district. The method of this program is a workshop that is carried out with the methods of lectures, discussions, and consultations, with materials such as the introduction of scientific work, techniques for writing scientific works, and strategies for making articles and submitting them to national journals. To find out the success of the activity, evaluation is done by doing pretests and posttests with asking questions about the writing of scientific work. The results were that 29 participants (97%) stated that the material provided was perfectly suitable for their needs, 1 participant (0.3%) said it was suitable, 30 participants (100%) said that the workshop was beneficial, and then 30 participants (100%) stated that they were motivated to write scientific writing after attending the workshop as well as to create scientific writing independently.